m6A transferase KIAA1429 mediates the upregulation of LncRNA LINC00968 promoting the progression of gastric cancer cells - Huijun Liu; Menghan Yang; Chunyue Zhang; Yanmin Zhang; Yan Wang; Yueda Chen (Hereditas)
Abstract Background The screening and monitoring of gastric cancer is still a clinical challenge. Both N6-methyladenosine (m6A) and lncRNAs have been evidenced as critical regulators of gastric cancer, but their interaction and potential in modulating tumor progression remain unclear. This study aimed to evaluate the function of lncRNA LINC00968 in gastric cancer biological processes, and we discovered the role of KIAA1429, a typical m6A eraser, in mediating LINC00968 function. Materials and methods The expression of LINC00968 was assessed using PCR and regulated by cell transfection. Cellular processes were evaluated by CCK8 and Transwell assays. The m6A modification and the interaction of LINC00968 with KIAA1429 were identified with Methylated RNA immunoprecipitation-qPCR. The regulatory effect of LINC00968 on miR-3202 and VIRMA was estimated by luciferase reporter assay. Results Significantly increased LINC00968 was observed in gastric cancer cells. Silencing LINC00968 suppressed gastric cancer cell growth and motility. m6A-modified sites were predicted in LINC00968 and overexpressing KIAA1429 enhanced the enrichment and stability of LINC00968 in gastric cancer and reversed the knockdown of LINC00968. The overexpression of KIAA1429 could attenuate the inhibitory effect of LINC00968 knockdown on gastric cancer cellular processes. LINC00968 could negatively regulate the expression of miR-3202, which further regulate VIRMA, the coding gene of KIAA1429, in gastric cancer cells. Conclusions LINC00968 contributes to the enhanced cell growth and metastasis of gastric cancer, which was mediated by KIAA1429-mediating m6A modification and the miR-3202/VIRMA axis.